The use of human antiretroviral drugs (ARVs) in broiler chicken and domestic pig farming in Tanzania - Zuhura I. Kimera; Emmanuel C. Balandya; Mecky I. N. Matee; Lisa V. Adams (Bulletin of the National Research Centre)
Abstract Background The use of antiretroviral (ARV) drugs in Tanzania has led to a significant reduction in morbidity and mortality and improved quality of life among people living with HIV infection. However, the ease of access and availability of the drugs has, in some cases, led to misuse of the ARV in areas such as animal farming, posing a risk of the emergence of ARV resistance. The study’s objective was to investigate the use of ARV in animal farming and the factors associated with ARV use. We conducted a cross-sectional study in three regions (Dar es Salaam, Iringa, and Mbeya) using focus group discussions. The researchers used NVivo 12 software for qualitative data analysis. Results A total of 113 participants participated in this study. The participants mentioned the use of veterinary, human, and local medicines to be prevalent. The drivers for such usage are disease treatment and prevention, growth promotion, counterfeited drugs, higher cost of animal feeds, profit maximization, market competition, advice from veterinary drug sellers, and easy availability and accessibility of medicines. New Castle, respiratory diseases, and diarrhea were the most common diseases affecting broiler chickens, while limb paralysis, swine fever, and skin diseases were prominent in domestic pigs. The Dar es Salaam region has a scarcity of extension officers compared to the Mbeya and Iringa regions. Almost all FGD participants reported hearing about the use of ARVs and family planning injectable and pills. Some of the participants agreed to use these drugs for growth promotion since they are effective. Conclusion High usage of veterinary, human, and other medicines, including ARVs, in animal production predisposes the Tanzanian community to public health threats, including antibiotic and antiretroviral resistance. We recommend implementing urgent mitigation strategies to control the misuse of human ARVs in animal production.